Invasion of Parthenium hysterophorus: Ecological Threats and Management Strategies in Kurram District, Khyber Pakhtunkhwa, Pakistan - Ali, Naveed; Ali, Farhad; Ullah, Shariat; Hussain, Wahid (Himalayan Biodiversity, 2025)
Parthenium hysterophorus L. (Asteraceae), commonly known as Parthenium weed, is an invasive annual herb that behaves as a perennial in Pakistan, severely impacting local biodiversity. In Khyber Pakhtunkhwa, particularly in District Kurram, it spreads across roadsides, waterways, and wastelands. A field survey was conducted from March 2022 to June 2023 assessed the distribution of Parthenium and its effects on native plants. Data was collected through 1m² quadrats, revealing 56 plant species from 21 families, including 18 annuals, 2 biennials, and 35 perennials. Three areas with significant Parthenium presence were selected, and three plant communities were identified: Parthenium-Dichanthum-Cynodon, Parthenium-Cynodon-Xanthium, and Parthenium-Cynodon-Taraxacum. The study recorded absolute density, relative density, absolute frequency, relative frequency, and importance values (IV) for Parthenium and other species. Asteraceae had the highest family importance value (FIV) of 478.16, followed by Poaceae (260.99), Fabaceae (24.8), and others. Soil analysis showed predominantly sandy loam and silty loam, with pH values between 7.10 and 7.15. Nutrient levels varied, with nitrogen (0.15-0.21%), phosphorus (1.99-7.50 mg/kg), potassium (105-131 mg/kg), and trace metals such as zinc (1.11-9.83 mg/kg) and iron (20.56-39.13 mg/kg). The study also examined control methods for Parthenium, including salt solution, urea, and herbicide, hand pulling, slashing, and burning. The findings provide valuable guidance for local farmers and communities on managing this invasive species. Given its rapid spread and poor management, Parthenium has become a major threat in Pakistan, especially in KPK, requiring immediate policy attention and quarantine measures to protect native plants and ensure optimal crop production.